Updated checklist of freshwater algal flora of Kurdistan region of Iraq: Checklist of algal flora of Kurdistan - Farhad Hassan Aziz; Alwan Qader Ahmed (Zanco Journal of Pure and Applied Sciences, 2022)
An updated checklist of 1812 taxa of freshwater algae is provided for the Kurdistan region of Iraq. The list comprises 426 Cyanophyta, 13 Rhodophyta, 87 Euglenophyta, 9 Cryptophyta, 18 Dinophyta, 13 Chrysophyta, 44 Xanthophyta, 643 Bascillariophyta and 559 Chlorophyta, representing 471 new additions to the last checklist of Kurdistan. References: Abdul-Jabar, R.A. (1981). An ecological study on Lesser Zab, M.Sc. Thesis, Univ. Sulaimaniyah, Iraq. (in Arabic). Abdulwahid, S.J. (2008). Aphycolimnological study on some springs within Harir sub district, Hawler, Kurdistan Region of Iraqi.M.Sc. Thesis, Univ. Salahaddin –Hawler, Iraqi Kurdistan Region. AHMED, A. Q. (2016). Phycolimnological Study on Some Springs around Safeen Mountain Area. M.Sc. Thesis. Salahaddin University, Erbil, Kurdistan Region -Iraq. Al-Naqshbandi, I. Y. R. (2002). A phycolimnological studies on impoundment and its main watershed. Ph.D. Thesis Duhok Univ. Kurdistan Region of Iraq. Al-Barzingy, Y.O.M. (1995). Phycological study within Erbil province, M.Sc. Thesis, Univ. of Salahaddin-Arbil. AL-Barzingy, Y.O.M.; Goran, S.M.A. and Toma, J.J. (2009). An Ecological study on Water in some Thermal Springs in Koya-Erbil, Iraq. J. of Education and Science. 22 (3): 36-48. Al-Hamed, M.I. (1976a). Limnological Investigations of Dokan reservior. Bull. Nat Hist. Res. Center Baghdad. 7(1): 91-109. Al-Naqshbandy, L.M. and Aziz, F.H. (2020). Batracospermum and Nostoc fromsprings and streams within Akri district, Duhok province. Not published. from Ph. D. Thesis, Department. of Environmental Health Science, College of Science, Salahaddin University-Erbil. Kurdistan- Region., Iraq. Al-Nimma, B.A.B. (1982). A study on the Limnology of the Tigris and Eupharates rivers. M.Sc. Thesis, Univ. Salahaddin. (in Part) Al-Saboonchi, A. A. Mohamed, A-R. M. and Barak, N.A. (1982). A study of phytoplankton in the Garma marshes, Iraq. Iraqi J. Mar. Sci. 1, (1): 67-78. Al-Shahwani, S.M.H (1980). A study on the primary productivity of Serchinar spring. M.Sc. Thesis, Univ. Sulaimanyiah. Aziz, F. H. C. (2008) Further contribution of algae in higher mountain areas to Iraqi Salahaddin University Hawler 20, 4 :63- 81. Aziz, F. H. and Ganjo, D.G. A. (2004). Observations on the ecology and limnology in a permanent polluted pond in Erbil city. J. of Pure and Applied Sci., Salahaddin Univ.-Erbil, Iraq. 16(1):43 52. Aziz, F. H. (1997). A phycological study with particular reference to Rawanduz river path within Arbil province, Iraq. Ph.D. Thesis, Univ. of Salahaddin-Erbil, Iraq. Aziz, F. H. (2001). Changes in epilithic algal community responses to chemico-physical changes in a mountainous stream. Sci. J. Babylion Univ., 13(5):905-917. AZIZ, F. H. (2011). Checklist of the Algae in Iraqi Kurdistan Region. Zanco J. of Pure and Applied Science. Salanaddin University. 23(3), pp. 31-72. Aziz, F. H. (2015) New Record of the Genus Porphyridium purpureum from Kurdistan. Journal of Advanced Laboratory Research in Biology E-ISSN: 0976-7614, Volume 6, Issue 2, PP 54-57. Aziz, F. H. and Yasin, S. A. Twenty- five new records of algae in eight artificial fish ponds in Erbil. ZANCO Journal of Pure and Applied Sciences, (2019), 31(1);1-16. Aziz, F. H. and Muhammed, A. Q. A. (2016). Twenty new records of Algae in some springs around Safeen mauntain area. Journal of advanced laboratory research in biology, vol. 8 (3) July 2016, ISSN: 0976- 7614. Aziz, F. H. and Rasoul, B. H. (2016). Thirtytwo algae new records reported in ponds at Gwer sub district Erbil – Kurdistan Region Iraq. Bull. Iraq nat. Hist. Mus. 14 (1): 27-42. Aziz, F. H., Bapeer, U. H. K.and Najmadden, S. K. (2017). Forteen algae new records reported in five artificial ponds in the main parks within Erbil city, Kurdistan region, Iraq. Mesopotamia environmental journal, vol.4, no.1, pp (12- 22). Aziz, F. H., Hassan, F. M. and Rasoul, B. H. (2014). An ecological obserbation on inland water ecosystem in Erbil – Iraq Kurdistan with particular reference to blue green algae glaucospira. Bagdad science journal vol. 11 (3) 2014. Aziz, F.H. and Ganjo, D. G. A. (2002). Nutrient status and algal flora in the halgurd (Hasarost) mountain area within Arbil province, Iraq. Zanco, Sci. J. Duohok Univ. 5(2):1-12. Bilbas, A. H. A (2004). Aphycolimnological study on some springs within Erbil province .M-Sc-Thesis, Univ. Salahaddin – Hawler, Iraqi Kurdistan Region. DARBANDI, B. H. R. (2013). A phycolimnological study in ponds near Greater Zab River in Gwer area –Erbil. Msc. Thesis. Univ.of salahaddin. Fadhil, A. M. (2011). Drought mapping using Geoinformation technology for some sites in the Iraqi Kurdistan region. International Journal of Digital Earth, Vol. 4, No. 3, May 2011, 239_257. Goran S.M.A. (2006). Limnology and Non-diatom phytoplankton composition of Dilope Spring and Kesnezan Impoundment. M.Sc. Thesis, College of Science, Univ. of Salahaddin, Erbil, Iraq. Hamadamen, A. R. (2015). Eco- Phycological study of the Qandil mountain streams/ Sulaimani. M.Sc. Thesis. Univer.of Salahaddin- Erbil. Hameed, H. M. (2013). Water harvesting in Erbil Governorate, Kurdistan region, Iraq Detection of suitable sites using Geographic Information System and Remote Sensing, M.Sc. thesis Lund University. Hinton, G.C.F. and Maulood, B.K. (1979a). Freshwater diatoms from Sulaimaniyah, Iraq. Nova Hedwigia, 31(1+2): 449-466. Hinton, G.C.F. and Maulood, B.K. (1979b). Some observations on the diatom flora of Serchinar spring, Sulaimaniyah. Iraq. Br. Phyc. J., 14:125. Hinton. G.C.F. and Maulood, B.K. (1979c). A modified membrane filtration method for phytoplankton enumeration in marine and freshwater ecosystem. Tropical Ecology., 192-194pp. Hirano, M. (1973). Freshwater algae from Mesopotamia. Kyoto University, 24:105-19. Ibrahim, A.M.K. (1981). A study on the algal ecology of spring in Sulaimaniyah province. M.Sc. Thesis, Univ. ofSalahaddin. JOHN, D. M., WHITTON, B. A., & BROOK, A. J. (2011). The Freshwater Algal Flora of the British Isles. 2ed edition printed in Cambridge University Press. Khamees, H.S. (1979). An ecological study on water pollution in Tanjero. M.Sc. Thesis. Univ. of Sulaimaniyah, Iraq (in Arabic). Kolb, R.W. and Krieger, W. (1942). Susswasserlagen aus Mesopotamen and Kurdistan. Ber. Dtsch. Bot. Gse., 60:336- 355. KOMAREK, J., and ANAGNOSTIDIS, K. (2005). Cyanoprokaryota. 2nd part: Oscillatoriales. Elsevier, Munchen. Germany 1-759. MAMLESI, F. O. M. (2010). Engineering geological study of rock slope stability along the Dokan-Khalakan road, Kurdistan Region, NE-Iraq. M.Sc. Thesis. University of Sulaimaniyah. Maulood, B.K. (1991). Contribution to the algal flora of some springs and strams in the Derbendikan. Iraqi J. Sci., 3 3, (2): 668-679. Maulood, B.K. and Hinton, G.C.F. (1978a). An ecological study on Serchinar water, chemical and physical aspects, Zanco, Series A, 4(3): 93-117. Maulood, B.K. and Hinton, G.C.F. (1978b). Observation on the algal flora of Sulaimaniyah area; Green and blue-green, alae. Zanco, Sci, J. Univ. Sulaimaniya, Iraq, Series A, 4:55-75. Maulood, B.K. and Hinton, G.C.F. (1979). Techoplanktonic diatoms from a stenothermal spring in Iraqi Kurdistan. Br., Phycological, J. 14:175-183. Maulood, B.K.; Hinton, G.C.F. and Al-Dosky, H.S. (1980). A study on the blue green algal flora of Erbil province, Iraq. Zanco. Series A, 6:67-90. MAULOOD, B. K., HASSAN, F. M., AL -LAMI, A. A. TOMA, J.J. & ISMAIL, A. M. (2013). Checklist of Algal Flora in Iraq. 1st edition, published in the republic of Iraq, by ministry of environment, Bagdad. Najmadden, S. K. (2017). Phycolimnological study of the water bodies in the main parks within erbil city – KRI. MSc. Thesis Salahaddin University, Erbil, Kurdistan Region – Iraq. Raoof, L.Y. (2002). Phycolimnological study on Duhok impoundment and its main watershade. Ph.D. Thesis Duhok, Univ.College of Science. Shaban, A.A. (1980). An ecological study on the phytoplankton of Dokan lake. M.Sc. Thesis, Univ. of Sulaimaniyah Iraq, (in Arabic). SHARIF, CH. M. (2016). Phycolimnological study on some springs within Zrarati area in Erbil province, Kurdistan Region, Iraq. M.Sc. Thesis. Salahaddin University, Erbil, Kurdistan Region -Iraq. Sofi, B. A. A. (2008). An ecological study on the main sewage channel of Erbil City, with particular reference to self purification. Msc. Thesis, Univ. of Salahaddin – Hawler, Iraqi Kurdistan Region. STEVENSON, R. L., BOTHWELL, M. L. & LOWE, R. L. (1996). Algal Ecology: Freshwater benthic ecosystems. Academic Press. New York. Toma, J., J. and Aziz, F., H. (2021a). New records of algae in Shaqlawa District, Erbil, Kurdistan Region of Iraq.ANJS, Vol. 24(3), pp. 55 – 62. Toma, J., J. and Aziz, F., H. (2021b). Algal study in springs and streams from Shaqlawa district, Erbil Province /Iraq- Zygnematales. Accepted for Publication in Iraqi Journal of Science Vol.63 (2). Toma, J., J. and Aziz, F., H. (2021c). Algal study in springs and streams from Shaqlawa district, Erbil Province, Iraq – Euglenophyta. Baghdad Science Journal, P- ISSN: 2078- 8665, E- ISSN: 2411- 7986. Toma, J., J. and Aziz, F., H. (2021d). Algal study in springs and streams in Shaqlawa district, Erbil province – Iraq- Chlorophyceae without Zygnematales. Accepted for Publication in Iraqi journal of Agricultural. Toma, J., J. and Maulood, B., K. (2013). Cyanophyata recorded in Erbil, Kurdistan region of Iraq. Current world environment, 2013,8 (1). Yasin, S. A. (2019). Phycolimnological Study of Some Artificial Fish Ponds within Erbil Province. MSc. Thesis Salahaddin University, Erbil, Kurdistan Region – Iraq. Zewayee, F.A.Q. (2011). A Phycolimnological study on some springs in mountain area within Erbil province. M.Sc. Thesis, Salahaddin University-Erbil. College of Science Education, Biology Dep.